Strengthening Business Success using Entrepreneurial Personal Independence and Entrepreneurial Competence - Iffan, Muhammad; Firmansyah, Rizal; Novianti, Windi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study was to find out the responses of respondents regarding Entrepreneurial Personal Independence, Entrepreneurial Competence, and Business Success, and to determine the effect of Entrepreneurial Personal Independence and Entrepreneurial Competence on Business Success at Distro in The Hallway Space, either partially or simultaneously. This study uses descriptive and verification methods with a quantitative approach, including validity tests, reliability tests, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing using the t-test and F-test. The sample in the study was 40 business owners. Data collection techniques by distributing questionnaires and conducting interviews with business owners. The results of the study show that Entrepreneurial Personal Independence, Entrepreneurial Competence, and Business Success at Distro the Hallway Space Bandung City are generally included in the fair category. The results of hypothesis testing show that Entrepreneurial Personal Independence and Entrepreneurial Competence have a positive and significant effect on Business Success either partially or simultaneously. This research is expected to be a reference for business owners to be able to increase Business Success by considering Entrepreneurial Personal Independence and Entrepreneurial Competence as determinant factors.